2011
DOI: 10.1111/j.1748-0361.2011.00382.x
|View full text |Cite
|
Sign up to set email alerts
|

Admission Factors Predicting Family Medicine Specialty Choice: A Literature Review and Exploratory Study Among Students in the Rural Medical Scholars Program

Abstract: Statements of interest, intentions, plans, and decisions regarding family medicine should be elicited at the time of RMSP admission interview. Strong attachment to home community and commitment to serving and living in a rural area are also important. Students whose introduction to medicine was informed through shadowing or observing in urban hospitals should be considered less likely to become family physicians. Larger sample size studies are needed to assess the role of gender, race, marital status, size of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 25 publications
2
16
0
Order By: Relevance
“…The medical school ethos and curriculum are another variables that seem to affect future career plans connected with specialty choices (Avery et al 2012 ). The curricula in Polish medical universities are mostly traditional ones, based on lectures, seminars and laboratories ending with examinations.…”
Section: Discussionmentioning
confidence: 99%
“…The medical school ethos and curriculum are another variables that seem to affect future career plans connected with specialty choices (Avery et al 2012 ). The curricula in Polish medical universities are mostly traditional ones, based on lectures, seminars and laboratories ending with examinations.…”
Section: Discussionmentioning
confidence: 99%
“…Self-identity including socioeconomic and geographic background of the physician was one of the driving forces identified together with a sense of responsibility and commitment to the community as well as the opportunity for personal development. Community influence with a strong attachment to original home community has also been invoked as a determinant of graduates ultimately practicing in an underserved community [10]. …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that factors associated with choosing GM/FM as a career are older age ( 7 , 8 ), gender (being a female) ( 9 ), being married ( 7 ), rural background (e.g., rural origin and rural high school graduation) ( 7 , 10 ), parents’ socioeconomic status ( 7 ), lifestyle considerations ( 11 , 12 ), working hours ( 13 , 14 ), low-income expectations ( 7 , 15 17 ), lower prestige ( 7 , 15 17 ), lower job-related ambition ( 15 ), intent for rural practice ( 7 ), longitudinal and close relationship with patients ( 9 , 11 , 12 , 16 , 17 ), no plan for a career in research ( 7 , 17 ), presence of a FM role model ( 7 , 16 , 18 ), and social need ( 16 ). More students might consider careers in primary care if they were exposed to more experiences in primary care ( 5 , 9 , 16 , 19 ).…”
mentioning
confidence: 99%